Experiments for analysis of video transmission via ATM - Pissioli, Mauricio (2002)
A large quantity of data of different types and priorities pass through on high-speed networks. A relevant part of these data, like continuous media (audio, video, and so), need a control of its Quality of Service (QoS). This paper describes experiments on the characteristics of the ATM network technology that provide support to quality video streaming transmission. The experiments were realized considering QoS, connection admission control, network congestion, transmission priorities and bandwidth demand associated to applications and network configuration. Three basic kinds of videos were analyzed-movies (smooth movies), sports (action movies) and talking head movies. Data about video transmission were collected from an ATM switch, showing results that can be used in the future on ATM channel mapping to multimedia data distribution (in applications like Interactive TV and Video-on-Demand, for example).